MINERALOGY OF CRYSTALLIZED MELT INCLUSIONS FROM GARDINER AND KOVDOR ULTRAMAFIC ALKALINE COMPLEXES: IMPLICATIONS FOR CARBONATITE GENESIS - Veksler I.V.; Nielsen T.F.D.; Sokolov S.V. (My University, 1998)
Cumulus olivine, clinopyroxene, melilite and perovskite from silicate rocks and carbonatites of the Gardiner (East Greenland) and Kovdor (Kola Peninsula) ultramafic alkaline complexes contain primary melt inclusions crystallized into aggregates of daughter minerals. The petrography and homogenization temperatures of the inclusions constrain the fractionation paths and the formation of carbonatites in the complexes. Carbonated melanephelinite was parental to both complexes and early cumulates (dunite, olivinite, peridotite and melteigite) are comparable. The common occurrence of phlogopite and amphibole in the inclusions and in the host rocks indicates that these were important liquidus phases. In both complexes the fractionation of phlogopite and amphibole drove the melts towards Ca-rich (larnite-normative) compositions. At the ijolite stage the evolutionary trends are believed to separate and the evolved larnite-normative melt produced calcite-bearing ijolite in Kovdor and melilitolite in Gardiner. The two assemblages are related by decarbonation reactions. A fractional crystallization origin is suggested for the Kovdor carbonatite, whereas the Gardiner carbonatite formed by liquid immiscibility in the course of melilite fractionation. Na–K–Ca and Na–Mg carbonates are common daughter phases and especially abundant in late-stage inclusions. Thus, all carbonatte melts in the two complexes are alkaline. Calcite carbonatites appear to be cumulates.